Airway smooth muscle inflammation is regulated by microRNA‐145 in COPD. Issue 9 (19th April 2016) - O'Leary, Lawrence; Sevinç, Kenan; Papazoglou, Ilektra M.; Tildy, Bernadett; Detillieux, Karen; Halayko, Andrew J.; Chung, Kian Fan; Perry, Mark M.
Abstract : Chronic obstructive pulmonary disease (COPD) is a common, highly debilitating disease of the airways, primarily caused by smoking. Chronic inflammation and structural remodelling are key pathological features of this disease, in part caused by the aberrant function of airway smooth muscle (ASM) cells under the regulation of transforming growth factor (TGF)‐β. miRNA are short, noncoding gene transcripts involved in the negative regulation of specific target genes, through their interactions with mRNA. Previous studies have proposed that mRNA‐145 ( miR‐145 ) may interact with SMAD3, an important downstream signalling molecule of the TGF‐β pathway. TGF‐β was used to stimulate primary human ASM cells isolated from healthy nonsmokers, healthy smokers and COPD patients. This resulted in a TGF‐β‐dependent increase in CXCL8 and IL‐6 release, most notably in the cells from COPD patients. TGF‐β stimulation increased SMAD3 expression, only in cells from COPD patients, with a concurrent increased miR‐145 expression. Regulation of miR‐145 was found to be negatively controlled by pathways involving the MAP kinases, MEK‐1/2 and p38 MAPK. Subsequent, overexpression of miR‐145 (using synthetic mimics) in ASM cells from patients with COPD suppressed IL‐6 and CXCL8 release, to levels comparable to the nonsmoker controls. Therefore, this study suggests that miR‐145 negatively regulates pro‐inflammatory cytokine release from ASM cells in COPD by targeting SMAD3 . Abstract :